2020
DOI: 10.14202/vetworld.2020.1229-1233
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cardiac variables using a new electrocardiography lead system in horses

Abstract: Aim: The objective of this study was to assess a new lead system method to improve electrocardiographic measurement in horses. Materials and Methods: Twenty-two horses with an average age of 8.8±0.8 years were enrolled in this study. Horses were divided into two groups, consisting of a control group (n=11) and athlete group (n=11). Electrocardiography (ECG) and echocardiography were performed to provide information on the structure and function of the heart. Two lead systems, base apex and modified pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
4
7
0
Order By: Relevance
“…Previously it has been shown that the QT interval is prolonged in trained horses similar to findings in human athletes 12,54 . We, on the contrary, observed a shortening of the QTc in the trained horses that mostly had monophasic positive T wave deflections whereas the untrained horses primarily had biphasic T waves.…”
Section: Discussionsupporting
confidence: 74%
“…Previously it has been shown that the QT interval is prolonged in trained horses similar to findings in human athletes 12,54 . We, on the contrary, observed a shortening of the QTc in the trained horses that mostly had monophasic positive T wave deflections whereas the untrained horses primarily had biphasic T waves.…”
Section: Discussionsupporting
confidence: 74%
“…It was possible that muscle tremors, shivering, and restlessness may be minimized with a ground electrode attached in an unobtrusive place such as the xiphoid position. The P wave was the dominant bifid configuration in the base-apex lead method, similar to previous studies [ 12 , 18 ]. The bifid P wave in horses revealed first the depolarization of the right atrium and subsequently the depolarization of the left atrium.…”
Section: Resultssupporting
confidence: 89%
“…The different ECG parameter values in this study are found to be in agreement with previous study conducted by Cherdchutham et al . [ 18 ]. We found that the repositioning of the ground electrodes did not affect the amplitude or duration of P waves and QRS complexes, T duration, and PR interval but did influence the QT interval.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations